Personnel training for the security and defense sector as a prerequisite for ensuring the national security of Ukraine - V. V. Sokurenko (Law and Safety)
It has been established that one of the necessary steps in the direction of ensuring national security and citizens’ protection of rights and freedoms is strengthening the institutional, defense and security capabilities of bodies belonging to the security and defense sector. In this regard, it has been argued that a necessary prerequisite for national security is to ensure quality training of specialists for the security and defense sector, which will be able to respond in a timely manner to various crises.